The Influence of Transformational Leadership on Organizational Culture - Tedy Darmawan Sih Sertiarto; M. Agam Prayogi; Eisha Lataruva; Ismi Darmastuti (Arthatama: Journal of Business Management and Accounting, 2025)
This study aims to examine the influence of transformational leadership on organizational culture using a Systematic Literature Review (SLR) approach. The main focus is on how the dimensions of transformational leadership, namely motivation, can be enhanced through training and contribute to forming an adaptive, innovative, and collaborative organizational culture in various sectors. This review follows the PRISMA guidelines and analyzes peer-reviewed articles sourced from Scopus, ScienceDirect, and ProQuest databases within the 2020–2025 publication range. The final results show that only a limited number of articles met all inclusion criteria. Nevertheless, the findings consistently indicate a positive relationship between transformational leadership and the development of organizational culture. Transformational leadership is considered effective in cultivating a positive organizational culture. However, its success is highly influenced by contextual factors such as organizational type, industry sector, and readiness for change. The limited number of studies meeting the inclusion criteria suggests a need to relax selection standards or broaden methodological approaches in future research to yield more comprehensive insights.